Factors associated with poor outcomes in patients with maple syrup urine disease in a tertiary government hospital: A retrospective cohort study - Christine Mae S. Avila; Mary Ann R. Abacan (JIMD Reports)
Abstract This study aims to determine the factors associated with mortality and neurodevelopmental morbidity in patients with Maple Syrup Urine Disease (MSUD) seen at a tertiary hospital in the Philippines during a 10‐year period. The medical records of patients diagnosed with MSUD seen at Philippine General Hospital (PGH) from 2010 to 2019 were reviewed. Socioeconomic, healthcare, and clinical factors were determined. The association of these factors with mortality and neurodevelopmental morbidity (developmental delay and seizures) was evaluated through statistical analysis. Seventy‐five records of MUSD cases were available for review. Fifty‐five percent of patients had developmental delay and 57% had seizures. Mortality rate was 25%. Age at collection of newborn screening (OR 1.29, 95% CI 1.04–1.60, p = 0.022) and the number of metabolic crisis in a year (OR 5.4, 95% CI 1.5–19.0, p = 0.008) were significantly associated with increased mortality. Male sex (OR 2.78, 95% CI 1.06–7.26, p = 0.037) and dietary non‐compliance (OR 2.56, 95% CI 1.48–4.42, p = 0.001) were associated with increased developmental delay. Age above 5 years (OR 6.5, 95% CI 1.15–36.57, p = 0.034) and nosocomial infections (OR 6.96, 95% CI 1.33–36.53, p = 0.022) were associated with occurrence of seizures. In conclusion, among our cohort of MSUD patients, the age at collection of newborn screening and the number of metabolic crises annually were associated with increased mortality. Male sex, dietary non‐compliance, and nosocomial infections were associated with increased neurodevelopmental morbidity.